Partial-Hand Prosthesis Users Show Improved Reach-to-Grasp Behaviour Compared to Transradial Prosthesis Users with Increased Task Complexity. Issue 6 (2nd November 2022) - Alterman, Bennett L.; Keeton, Emily; Ali, Saif; Binkley, Katrina; Hendrix, William; Lee, Perry J.; Wang, Shuo; Kling, James; Johnson, John T.; Wheaton, Lewis A.
Abstract: Approaches to improve outcomes after upper-extremity amputation remain poorly understood. Examining prosthesis-use at different levels of loss elucidates motor control challenges. Non-amputated participants completed simple and complex reach-to-grasp actions using a body-powered transradial or partial-hand prosthesis simulator. We hypothesised that increased task complexity and participants using a partial-hand device would show greater functional adaptation compared to participants using a transradial device. Partial-hand users demonstrated variable grasp postures and higher reach peak velocities in the complex, but not simple, task. All groups showed decreases in movement duration in the complex task, but only partial-hand users improved in the simple task. These behavioural changes suggest how device level and task may influence prosthesis-use, with relevance to amputation rehabilitation.